Phosphogypsum as Fertilizer: Impacts on Soil Fertility, Barley Yield Components, and Heavy Metals Contents - M Barka Outbakat; Moussa Bouray; Redouane Choukr-Allah; Mohamed El Gharous; Kamal El Omari; Khalil El Mejahed (Plants)
According to the FAO, 828 million people were facing acute food insecurity in 2021. Fertilization is a critical input factor in crop production and food security achievement. Therefore, fertilization is a critical input factor in crop production and food security achievement. However, there is room for improvement in the application of fertilizers in certain regions. Thus, new fertilizers with a relatively low cost could enhance farmers’ access to these essential inputs. Phosphogypsum (PG) is used as fertilizer because it contains many nutrients essential for plant growth, including calcium, sulfur, and phosphorus. A two-year field experiment was conducted using two Moroccan PG products (PG1 and PG2, obtained from two different industrial sites), applied at four rates (0, 1.5, 3, and 4.5 t/ha). The aim was to assess the impact of PG source and rate on barley crops, including yield component, nutrients uptake, and heavy metals content. The study’s findings revealed that as the rate of PG application increased, there were significant enhancements in the number of spikes, tillers, grains, total biomass, grain yield, and thousand-grain weight. In fact, when compared to the control, the application of 1.5, 3, and 4.5 t/ha of PG led to a remarkable increase in grain yield by 21%, 34%, and 39%, respectively. Furthermore, the uptake of nutrients (N, P, K, Ca, Mg, and S) by the shoots and grains was significantly influenced by the PG application rates, with higher rates resulting in greater nutrient uptake. Notably, the application of PG had no discernible impact on the heavy metal content in shoots, grains, or soil.